Health Care Current Reviews 2019
DOI: 10.35248/2375-4273.19.07.244
|View full text |Cite
|
Sign up to set email alerts
|

Situation Analysis of Health Care System of Pakistan: Post 18 Amendments

Abstract: Objective of the study: The aim of this paper is to highlight the actions taken by the government in various health performance system domains post 18 th Amendment. Methodology: Health system performance domains were identified through the websites of WHO and Eastern Mediterranean Regional Office of WHO (EMRO). Then the actions required in various health system performance domains were identified and the literature related to health system performance domains and 18 th Amendment was reviewed through electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 20 publications
0
46
0
Order By: Relevance
“…In Pakistan, there have been concerns with healthcare management at the provincial level following devolution, although this is not universal as seen with the recent COVID-19 pandemic (40,74,85). This is a concern with over 40% of the population currently living below the poverty line, and high rates of co-payments at over 78% of total healthcare expenditure with potentially catastrophic consequences if family members become ill (74,(86)(87)(88). The situation has been made worse in Pakistan in recent years with a rise in both infectious and noninfectious diseases.…”
Section: General and Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, there have been concerns with healthcare management at the provincial level following devolution, although this is not universal as seen with the recent COVID-19 pandemic (40,74,85). This is a concern with over 40% of the population currently living below the poverty line, and high rates of co-payments at over 78% of total healthcare expenditure with potentially catastrophic consequences if family members become ill (74,(86)(87)(88). The situation has been made worse in Pakistan in recent years with a rise in both infectious and noninfectious diseases.…”
Section: General and Asiamentioning
confidence: 99%
“…Local production of essential preventative equipment is likely to grow across countries to reduce future shortages (61,62). Compounding the situation in Bangladesh, India, and Pakistan, certainly with respect to available resources to fund prevention and treatment of COVID-19, are also high prevalence rates of non-communicable diseases (NCDs) including coronary vascular disease (CVD), hypertension and diabetes (4,74,87,(95)(96)(97). This will necessitate changing models of care with increasing use of all healthcare professionals, exacerbated by the current situation with COVID-19 (98)(99)(100)(101).…”
Section: General and Asiamentioning
confidence: 99%
“…The health care delivery in Pakistan is considered as a neglected sphere of social security. A report indicated that the government allocation in health care is as low as 0.4% of its overall GDP, thereby nearly 78% of the population pays out of their pockets for health services in private health sectors [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The health care delivery in Pakistan is considered as a neglected sphere of social security. A report indicated that the government allocation in health care is as low as 0.4% of its overall GDP, thereby nearly 78% of the population pays out of their pockets for health services in private health sectors [24]. Adequate spending on public healthcare by the government ensures a robust functioning of healthcare delivery in the country.…”
Section: Discussionmentioning
confidence: 99%